Adjustable Electrical Dispersion Compensation in a 40-Gb/s Optical Single Sideband System - Madureira, M. A. M. (2006)
The efficiency of an adjustable electrical dispersion compensator (AEDC) in a 40-Gb/s optical single sideband system is investigated experimentally. The AEDC is implemented using a developed monolithic feed-forward equalizer whose performance can be optimized by adjusting the tap weights. Specifically, the AEDC contribution to the system performance improvement is achieved by synthesizing a suitable transfer function that shows group delay dependency on the frequency opposite to that of the fiber. Group velocity dispersions up to 272 ps/nm are experimentally obtained with a power penalty of less than 4 dB relative to the back-to-back situation without equalization.